Dynamic Power Cable Layout Design for 15MW Floating Offshore Wind Turbines: Part 1 - Configuration Analysis and Optimization - Doyoung Kwon; Hyun Kyung Kim; Joonmo Choung (한국해양공학회지)
A lazy wave configuration was designed and validated for a dynamic power cable connected to a 15MW floating offshore wind turbine (FOWT) in the Ulsan offshore region. The design variables included the starting position, length, and total buoyancy of distributed buoyancy modules (DBMs). The starting position of the DBMs refers to the absolute distance along the dynamic power cable from the hang-off point, with nine levels considered. The DBM lengths were divided into eleven levels, and the total buoyancy was analyzed at two levels: 140% and 230% of the suspended weight of the dynamic power cable. One hundred and ninety-eight models were developed based on these parameters and subjected to parametric static analysis. Three-dimensional response surfaces for hang-off tension, Ez angle, and minimum bend radius (MBR) were compared to identify the optimal layouts. Two configurations were proposed for each buoyancy level, revealing a trade-off between the MBR and Ez angle: increased buoyancy improved MBR but negatively impacted Ez angle. This inverse relationship underscores the need for careful optimization. Future work will involve fully-coupled load analyses of the FOWT under ultimate and fatigue limit state conditions to assess the structural integrity and long-term performance in the extreme environment of Ulsan offshore waters.